Academic Management and Teaching Performance, according to the students of a private university in Lima, Peru - Surco Salinas, Daniel Víctor (2018)
Currently, it should be noted that the Academic Management (GA) should be a key criterion for the management of educational institutions and also the Teaching Performance (DD) be framed in the institutional goals of these organizations. The objective of the research was to determine the degree of relationship that exists between the GA and the DD, according to the perception of the students of a private university. Cronbach's Alpha presented acceptable indexes of 0.934 for GA and 0.946 for DD. In the validity of the instruments, 0.823 was reached for GA and 0.814 for DD. The results of the investigation have shown that there is a moderate and positive Spearman (rho) correlation between the GA and DD with a value of 0.629, while the Spearman correlation between the GA and the DD dimensions varies between the values 0.432 and 0.608, which are significant.